Analisis strategi manajemen PT. Derma Kusuma Artha dalam mengembangkan usaha - Widyaningsih Widyaningsih; Endang Masitoh W; Purnama Siddi (Penerbit Goodwood, 2020)
Purpose: This study aims to analyze the capital budgeting and business feasibility of PT DKA and its development strategy. Research methodology: This research was a qualitive research with a case study approach. The data collection method used was survey research by estimating the project costs, sales data, organizational structure and assignments for each section. The analyzed aspects were the market and its marketing, the management and its organization, and also the financial by using NPV and IRR measurement. The analysis SWOT was for market aspect and its marketing. Results: The business development plan which conducted by PT DKA is based on the market aspect and its marketing, the management and its organization also the financial aspect. The development business strategy in the market and marketing aspect which conducted by PT DKA is the alternative strategy of SWOT analysis. Limitations: The limitiations of this research were not all of the business feasibility aspects were analyzed. In addition it was only conducted at PT DKA. Contribution: This research contributes to affirm that the business is appropriate also as an alternative reference for business negotiation, especially with the investors. Keywords: Business development, NPV, IRR